Promoting Research and Innovation for Cultural Herit-age in Cyprus through the CONNECTING Infrastructure Project - Argyrou, Argyro; Gravanis, Elias; Hadjipetrou, Stylianos; Kafataris, Giorgos; Kyriakides, Nicholas; Kyriakidis, Phaedon; Lysandrou, Vasiliki; Michaelides, Kyriakos; Papakonstantinou, Apostolos; Skarlatos, Dimitrios; Vlachos, Marinos; Votsis, Renos; et al. (My University, 2024)
The "Research and Innovation Knowledge Centre for Engineering in Heritage" project, in short CONNECTING, aims to establish a knowledge centre equipped with advanced sensors and platforms such as Vertical Take-off and Landing (VTOL) drones, cameras, LiDAR systems, laser scanners, and various other sensors to support research on cultural heritage sites and monuments, both on land and underwater. The knowledge centre will serve as a hub for supporting local research in Cyprus dealing with cultural heritage. The project brings to-gether a multidisciplinary team involving experts from the domains of geomatics, civil engineers, Information, Communication and Technology (ICT)experts, ar-chaeologists, and heritage managers. This collaborative effort will enable the se-lection of appropriate methods, techniques, and tools to support heritage sites, management, and preservation. The project will also develop a cloud Data Centre to store and share evidence, results, services, and products. This paper serves as an introduction to the scope and objectives of the project, while it also outlines the infrastructure that is expected to be acquired and hosted at the Cyprus Uni-versity of Technology premises.
Keywords: Cultural Heritage; Documentation; Remote Sensors; UAV; Earth Observation; Underwater Object Detection